STRENGTHENING CHARACTER EDUCATION THROUGH ECOLOGICAL LITERACY IN THE FOLKLORE OF THE GREAT KAPOK TREE FOR PRIMARY SCHOOL STUDENTS - Zaitun, Zaitun; Qurrotaini, Lativa; Novita, Pipit; Rahman, Irpan Ali; Rahman, Taofix (Linguistik : Jurnal Bahasa dan Sastra, 2024)
This research is motivated by the importance of instilling awareness of the importance of protecting the environment from an early age. Strengthening character in environmental care has a positive impact on the survival of the next generation. The behaviour of not caring about the destruction of nature as a result of human actions is very dangerous if it is passed on to the younger generation, so it is necessary to strengthen the character of environmental care from an early age.  This research aims to provide the right choice of literary ecological literacy material as an effort to strengthen the character of environmental care in students in elementary schools. Imaginary characters in literary works become real examples for student character development. Strengthening the character of environmental care based on moral values in folklore needs to be conveyed so that students will have character intelligence to care for their environment. This research uses descriptive qualitative methods and literature study of story narratives, character behaviour, and dialogue and monologue sequences that illustrate the value of character education. The subject of this research is the folktale The Great Kapok Tree Tree: A Tale of The Amazon Rain Forest by Lynne Cherry. The findings show that The Great Kapok Tree folktale represents the values of environmental care in realising character strengthening including: environmental care as a system and awareness in environmental development. Thus, the folklore of The Kapok Tree contains the values of environmental care character education so that it can be an alternative solution for reading material on meaningful literary literacy.